Discharge protocol in acute pancreatitis: an international survey and cohort analysis - Nagy, Rita; Ocskay, Klementina; Sipos, Zoltán; Szentesi, Andrea; Vincze, Áron; Czakó, László; Izbéki, Ferenc; Shirinskaya, Natalia V; Poluektov, Vladimir L; Zolotov, Alexandr N; Zhu, Yin; Xia, Liang; et al. (Scientific reports, 2023)
There are several overlapping clinical practice guidelines in acute pancreatitis (AP), however, none of them contains suggestions on patient discharge. The Hungarian Pancreatic Study Group (HPSG) has recently developed a laboratory data and symptom-based discharge protocol which needs to be validated. (1) A survey was conducted involving all members of the International Association of Pancreatology (IAP) to understand the characteristics of international discharge protocols. (2) We investigated the safety and effectiveness of the HPSG-discharge protocol. According to our international survey, 87.5% (49/56) of the centres had no discharge protocol. Patients discharged based on protocols have a significantly shorter median length of hospitalization (LOH) (7 (5;10) days vs. 8 (5;12) days) p < 0.001), and a lower rate of readmission due to recurrent AP episodes (p = 0.005). There was no difference in median discharge CRP level among the international cohorts (p = 0.586). HPSG-protocol resulted in the shortest LOH (6 (5;9) days) and highest median CRP (35.40 (13.78; 68.40) mg/l). Safety was confirmed by the low rate of readmittance (n = 35; 5%). Discharge protocol is necessary in AP. The discharge protocol used in this study is the first clinically proven protocol. Developing and testifying further protocols are needed to better standardize patients' care.
Keywords: hospitalizace; Pancreatitis; propuštění pacienta; kohortové studie; Patient Discharge; akutní nemoc; Cohort Studies; lidé; Acute Disease; pankreatitida; Hospitalization; Humans